2021
DOI: 10.1177/1742271x21998721
|View full text |Cite
|
Sign up to set email alerts
|

Can shear wave elastography be utilized as an additional tool for the assessment of non-mass breast lesions?

Abstract: Introduction We aimed to describe shear wave elastography parameters of non-mass lesions of the breast and to assess the measures of diagnostic accuracy of shear wave elastography in the differentiation of non-mass lesions compared with conventional ultrasound, using histopathologic results as the reference standard. Methods This retrospective study included breast ultrasound-detected non-mass lesions with a confirmed pathologic diagnosis during a two-year study period. B-mode ultrasound and shear wave elastog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 26 publications
1
4
0
1
Order By: Relevance
“…We found that malignant breast lesions had higher stiffness than benign breast lesions. Similar results have been reported in other studies (23,24). Among the malignant breast lesions, invasive ductal carcinomas (11/18) were the most common pathological type in our study.…”
Section: Discussionsupporting
confidence: 93%
“…We found that malignant breast lesions had higher stiffness than benign breast lesions. Similar results have been reported in other studies (23,24). Among the malignant breast lesions, invasive ductal carcinomas (11/18) were the most common pathological type in our study.…”
Section: Discussionsupporting
confidence: 93%
“…Another concern was selection bias. In our meta-analysis, the total malignancy rate was 51%, but studies [10,23] have shown that NMLs have only about a 2% risk of malignancy, which is important. The main reason for this is clinical management.…”
Section: Discussionmentioning
confidence: 65%
“…However, Aslan et al's study [18] did not use a clear measurement index or cut-off value. Five studies [7,[20][21][22][23] did not mention whether patients were enrolled consecutively.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Dağılıma baktığımızda ise Park ve ark. artırarak, gereksiz biyopsi sayısını azaltabildiği bildirilmiştir [10,19,26]. Hong ve ark.…”
Section: Benign Ve Malign Lezyonlarda Histolojik Korelasyonunclassified